Kritik terhadap Pemikiran Kontroversial Bercorak Panteistik di Tengah Umat Islam dalam Karya Syaikh Abdus Shamad Al-Palimbani Abad ke-18 - Arafah Pramasto (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
Sufism is a philosophy that emerged among Muslims in 9th. Century A.D. It emphasises on the concept of bathiniya (esoteric) in the practicing of Islam. Among several figures propagating Sufism, two of them were Al-Hallaj in Middle East and Sheikh Siti Jenar in Indonesian Archipelago. Both were accused of spreading ideas of Panhteism (i.e. belief in Allah and his creations as one entity), which consequently resulted in Sufism being considered ‘Heresy’ and a ‘Stray idea’ by the orthodox Muslims. Sheikh Abdus Shamad Al-Palimbani, a Sufi Ulema born in Palembang (1737 AD) wrote critiques for Sufism in his three writings. The first book called ‘Kitab Hidayatus Shalikin’ in which he said that Allah is different with his creation. The second book, ‘Kitab Tuhfah Ar-Raghibin’ in which he rejected the concept of ‘Hulul’ (i.e. the belief that Allah is in creation), and lastly the ‘Kitab Siyarus Salikin’ that explored human’s awarness of their ‘lust’ which he believed is a gateway to understand the distinction between Allah’s divine reality and human existence.